2017
DOI: 10.1061/(asce)co.1943-7862.0001373
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Construction Workers’ Hazard Identification Skills on Their Visual Attention

Abstract: Eye-movement metrics have been shown to correlate with attention and, therefore, represent a means of identifying and analyzing an individual's cognitive processes. Human errors-such as failure to identify a hazard-are often attributed to a worker's lack of attention. Piecemeal attempts have been made to investigate the potential of harnessing eye movements as predictors of human error (e.g., failure to identify a hazard) in the construction industry, although more attempts have investigated human error via su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(46 citation statements)
references
References 58 publications
0
45
1
Order By: Relevance
“…Apart from a minor exception, these findings affirm many previous laboratory-based eye-tracking studies. However, some previous construction safety studies that used eye tracking in the laboratory found that workers with higher hazardidentification skills dwelt less on hazards (Hasanzadeh et al 2017a, b), a finding that diverges from the results obtained with the mobile eye tracker used in the current study. This discrepancy can be explained by comparing the experimental conditions in the laboratory and real world.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Apart from a minor exception, these findings affirm many previous laboratory-based eye-tracking studies. However, some previous construction safety studies that used eye tracking in the laboratory found that workers with higher hazardidentification skills dwelt less on hazards (Hasanzadeh et al 2017a, b), a finding that diverges from the results obtained with the mobile eye tracker used in the current study. This discrepancy can be explained by comparing the experimental conditions in the laboratory and real world.…”
Section: Discussioncontrasting
confidence: 99%
“…Attention is a selection process that determines which items are selected for subsequent processing (Wickens et al 2013). Balance between selective/focused attention (focus on only one stimulus) and divided/distributed attention (splitting attention between two or more tasks/objects) reflects both the amount and quality of information that an individual is able to perceive, process, and interpret from the environment (Hasanzadeh et al 2017a, b). In a dynamic environment, identifying relevant visual information and determining which information requires additional processing is important for individuals to maintain a safe level of performance (Kaber et al 2016).…”
Section: Role Of Attention In Situation Awarenessmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Hasanzadeh et al (2017c) expanded the application of eye-movement metrics to examine how working-memory load impacts a worker's attentional allocation and the detection of potential hazards in construction. Working memory (also known as short-term memory) refers to the mental workspace that offers limited capacity for maintaining information for short durations (Hitch and Baddeley 2017; Gevins et al 1998).…”
Section: Visual Attention and Construction Safetymentioning
confidence: 99%